A new ultra long-period fiber grating for measuring torsional characteristics. Issue 11 (25th June 2019) - Liu, Weiliang; Duan, Shujie; Du, Hang; Jiang, Hang; Sun, Cuiting; Jin, Xiren; Zhao, Lei; Geng, Tao; Tong, Chengguo; Yuan, Libo
ABSTRACT: In this paper, we proposed a novel kind of periodic helical ultra-long period fiber grating (U-LPFG) for measuring the torsion rate and distinguishing the torsion direction. The sensor was fabricated by spirally deforming a common fiber by local heating for 4 periods. This method of fabrication was not only easy to implement, but also further increased the sensitivity of the grating to the torsion because of the spiral structure. This paper introduced the torsional characteristics of this sensor in detail and drew some relevant conclusions. Experimental results showed that the twist sensitivity of 0.085 nm/(rad/m). Meanwhile, the temperature sensing characteristic of the proposed U-LPFG was also tested as 68 pm/°C within the range of 30 °C ∼210 °C. Therefore, this proposed sensor could achieve good results in simultaneously measuring the torsion rate and distinguishing the torsion direction, and it may have great potential in some practical applications.